Sastra Rempah Abad ke-19: Kajian Gastrokritik pada The History of Java dan Relevansinya dalam Wacana Kolonial dan Pascakolonial dalam Sastra Indonesia: Spice literature of 19th century: a study of gastrocriticism on The History of Java and its relevance in colonial and postcolonial discourse in Indonesian literature - Rohman, Saifur (Himpunan Sarjana Kesusastraan Indonesia (HISKI) Komisariat Kalimantan Timur, 2024)
This paper discusses The History of Java (first published in 1817 and published in Indonesian translation in 2014) by Thomas Stamford Raffles about the archipelago's spices, trade, and colonization. Since the arrival of the Portuguese in the easternmost of the archipelago in 1510, Western societies have been hunting for commodities that can be sold. They are middlemen, corporations, and hunters. The gastrocritical method developed by Endraswara was used to obtain literary data. The results of the primary data were linked intertextually to Nagara Krtagama (first published in 1365, then republished in 2009), Sair Rempah-Rempah by Mas Marco Kartodikromo (1919), and Aruna dan Lidahnya (2014) by Laksmi Pamuntjak. The study results show that the spice discourse not only discusses the